Goods and Services Tax (GST): A New Tax Reform in Malaysia - Mansor, Nor Hafizah Abdul; Ilias, Azleen (International Journal of Economics, Business and Management Studies, 2013)
The Goods and Services Tax (GST) is becoming one of the most prominent topics in Malaysia. The announcement by the Malaysian Ministry of Finance (MOF) in the Budget 2010 on the implementation of GST had created various reactions from practitioners, academicians, general public and most important businesses. GST is one of the tools that are proposed by the Government to reduce continuous deficit budget in Malaysia. This paper discusses the GST as a new tax reform in Malaysia, and covers several issues in order to enhance the understanding and readiness among Malaysian in adopting GST.